Effective interviewing and information gathering proven tactics to improve your questioning skills - Diamante, Thomas ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2013)
This book is an invaluable, instructional field manual for any professional who needs to obtain and interpret information gathered directly by and from people, without recourse to a technological intermediary, such as online search. In the role of interviewer, interrogator, or evaluator, there are many opportunities to get it wrong. Good information can go bad ... bad information can go good, but for the wrong reasons. Either way, without an understanding of process and context, free-standing information runs the risk of sending one in the wrong direction. As advanced as our information-gathering technology may be, it is still impossible to get inside the head of an interviewee by conducting a Google search; so hit them with the tactics spelled out in this book instead in order to protect yourself from being sent in the wrong direction.
Foreword -- Acknowledgments -- List of contributors -- A note to readers, complementing research with practice -- 1. Know your destination, map your path, and travel well -- 2. Interact, discover, and reflect -- 3. Uncover, reveal, and authenticate -- 4. The inference is the difference -- Index.
Part of: 2013 digital library.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF t.p. (viewed on May 28, 2013).
Keywords: Interviewing; executive coaching; assessment; interviewing; information; legal and regulatory; validity; EEO; information gathering; decision making; deception; selection; hiring; succession planning; human capital management